Intercultural Inquiry With Pre-service Efl Teachers - Stambouli , Manel Horiya Boudghene; Sarnou, Hanane (The Journal of Studies in Language, Culture, and Society, 2024)
Cultural extension in the intercultural digital era has amplified the importance of effective interpersonal communication among culturally different interlocutors, and this mainly aims to evade misunderstanding that may eventually lead to conflict. Indeed, professionals, businessmen and even ordinary people work to develop long-term economic, social and cultural relations with other cultural groups, yet global instability still threatens the world. Therefore, strengthening the skills required to encounter intercultural connections is becoming increasingly important at all levels, especially in education. Language educators are called upon to help learners assess their cultural and social differences and practices as community members. They are also required to guide students to accept and value otherness. In this sense, language educators should promote reflective environments where students can reflect upon culture and cultural diversity; they need to be open-minded and neutral agents who construct cultural experiences with students. Accordingly, this paper evaluates our ELT pre-service teachers’ readiness, as would be teachers, to develop their learners’ intercultural competences. To conduct this research study, the researchers used questionnaires as a primary tool to collect relevant data from 35 ELT pre-service teachers at Oran Higher School of Teachers. In a nutshell, this study highlights the importance of intercultural competence for teachers and learners in the age of globalization and diversity.